Screening and identification of a specific peptide binding to hepatocellular carcinoma cells from a phage display peptide library. (30th January 2014) - Guo, Yonge; Ma, Caixia; Li, Chunyan; Wu, Jinling; Zhang, Dan; Han, Juanjuan; Wang, Qixuan; Xu, Jinhui; Lu, Shaoying; Hou, Yingchun
<x xml:space="preserve">Abstract</x> To screen and identify the novel probe markers binding hepatocellular carcinoma specifically and sensitively, a phage‐displayed 12‐mer peptide library was used to make biopanning with the modified protocols on HepG2 cells. After four rounds of panning, the consensus sequences were obtained, and the PC28, a phage clone with most specific and sensitive binding to HepG2 cells, was identified as the best positive clone. The peptide probe HCSP4 (sequence SLDSTHTHAPWP) was synthesized based on the sequencing result of PC28. The specificity and sensitivity of HCSP4 were primarily analyzed using immunofluorescence, flow cytometry, and other methods. The results show that HCSP4 can bind to hepatocellular carcinoma cells with satisfactory specificity and sensitivity. It may be a promising lead candidate for molecular imaging and targeted drug delivery in the diagnosis and therapy of hepatocellular carcinoma. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.